Self-assembled Lyotropic Liquid Crystalline Phase Behavior of Monoolein-Capric Acid-Phospholipid Nanoparticulate Systems - Zhai, Jiali (Langmuir : the ACS journal of surfaces and colloids, 2017)
We report here the lyotropic liquid crystalline phase behavior of two lipid nanoparticulate systems containing mixtures of monoolein, capric acid, and saturated diacyl phosphatidylcholines dispersed by the Pluronic F127 block copolymer. Synchrotron small-angle X-ray scattering (SAXS) was used to screen the phase behavior of a library of lipid nanoparticles in a high-throughput manner. It was found that adding capric acid and phosphatidylcholines had opposing effects on the spontaneous membrane curvature of the monoolein lipid layer and hence the internal mesophase of the final nanoparticles. By varying the relative concentration of the three lipid components, we were able to establish a library of nanoparticles with a wide range of mesophases including at least the inverse bicontinuous primitive and double diamond cubic phases, the inverse hexagonal phase, the fluid lamellar phase, and possibly other phases. Furthermore, the in vitro cytotoxicity assay showed that the endogenous phospholipid-containing nanoparticles were less toxic to cultured cell lines compared to monoolein-based counterparts, improving the potential of the nonlamellar lipid nanoparticles for biomedical applications